2022
DOI: 10.15507/1991-9468.106.026.202201.027-041
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Teaching Quality, Social Support, and Career Self-Efficacy on the Career Adaptability Skills: Evidence from a Polytechnic in Indonesia

Abstract: Introduction. Changes in the industry impact the stable condition of working in a company or industry and it is not something that can be guaranteed again in the future. The proof is that there are many phenomena of job transfers or even layoffs in various business sectors due to COVID-19 pandemic. Many studies have examined the importance of developing career adaptability skills to face the changing needs of the industry. However, studies that discuss the mechanism of forming career adaptability skills involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…One of them is the instructional quality of the instructor when teaching in the classroom. The ability of teachers to mobilize students' confidence in their vocational abilities can strengthen students' career choices [25]. This means that career self-efficacy or students' beliefs about their career abilities also contribute to their increased perceptions of career choices.…”
Section: Literature Review 21 Career Construction and Instructional Q...mentioning
confidence: 99%
See 3 more Smart Citations
“…One of them is the instructional quality of the instructor when teaching in the classroom. The ability of teachers to mobilize students' confidence in their vocational abilities can strengthen students' career choices [25]. This means that career self-efficacy or students' beliefs about their career abilities also contribute to their increased perceptions of career choices.…”
Section: Literature Review 21 Career Construction and Instructional Q...mentioning
confidence: 99%
“…Positive sources of social support help individuals to believe in their abilities, especially regarding their career abilities [33]. Previous studies have also revealed that social support provides an impetus for increasing individual career adaptability [25]. Adolescents are more upbeat about their professional growth when their parents are supportive and supportive [34].…”
Section: The Role Of Social Support: Career Self-efficacy and Career ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The shift in technological progress in the 21st century also requires competency upgrades to match developments in entrepreneurship (Bican & Brem, 2020;Sahdan et al, 2017;Sahut et al, 2021). The era of digitalization inherent in the development of 21st-century technology is certainly a focus for upgrading its competence (Kholifah et al, 2021;Mahfud et al, 2022). In this era, comprehensive mastery of digital technology will provide views and develop ways of entrepreneurship more effectively and efficiently (Nambisan, 2017;Rippa & Secundo, 2019).…”
Section: Introductionmentioning
confidence: 99%